Is Nomophobia Problematic or Functional? A Perspective from Bifactor Structure. - Ren, Shixiu; Liu, Tour; Zhao, Xinlu; Yang, Haibo; Elhai, Jon D. (International Journal of Mental Health & Addiction, 2024)
With the extensive use of mobile phones globally, some people engage in excessive or problematic phone use behaviors. However, little is known regarding the latent structure of problematic mobile phone use. The current study employed the Chinese versions of the Nomophobia Questionnaire, Mobile Phone Addiction Tendency Scale, and Depression-Anxiety-Stress Scale-21 to explore the latent psychological structure of problematic mobile phone use and nomophobia and their associations with mental health symptoms. Results showed that a bifactor latent model best fit nomophobia, which contained a general factor and four unique factors involving the fear of being unable to access information, losing convenience, losing contact, and losing one's Internet connection. Results also showed significant correlations among latent factors of nomophobia, problematic mobile phone use, and mental health symptoms. Through these findings, we can conclude that two problematic mobile phone use behaviors share a common factor concerning excessive use, and nomophobia has independent unique factors concerning usable function. This study clarifies the structure of problematic mobile phone use, and it implies that we can distinguish problematic mobile phone use from functional use; further investigation of problematic mobile phone use is warranted.